Completeness of patient-held records: observations of the Road-to-Health Booklet from two national facility-based surveys at 6 weeks postpartum, South Africa - Ramraj, Trisha (J Glob Health, 2018)
BACKGROUND: Continuity of care is important for child well-being in all settings where postnatal retention of mother-infant pairs in care remains a challenge. This analysis reports on completeness of patient-held infant Road to Health Booklets (RtHBs), amongst HIV exposed and unexposed infants during the first two years after the RtHB was launched country-wide in South Africa. METHODS: Secondary data were analysed from two nationally representative, cross-sectional surveys, conducted in 2011-12 and 2012-13. These surveys aimed to measure early effectiveness of the national programme for preventing vertical HIV transmission. Participants were eligible for this analysis if they were 4-8 weeks old, receiving their six-week immunisation, not needing emergency care and had their RtHBs reviewed. Caregivers were interviewed and data abstracted from RtHBs. RtHB completeness across both surveys was defined as the proportion of RtHBs with any of the following indicators recorded: infant birth weight, BCG immunisation, maternal syphilis results and maternal HIV status. A partial proportional odds logistic regression model was used to identify factors associated with completeness. Survey sampling weights were included in all analyses. RESULTS: Data from 10 415 (99.6%) participants in 2011-12 and 9529 (99.2%) in 2012-13 were analysed. Overall, recording of all four indicators increased from 23.1% (95% confidence interval (CI)  = 22.2-24.0) in 2011-12 to 43.3% (95% CI = 42.3-44.4) in 2012-13. In multivariable models, expected RtHB completeness (ie, recording all four indicators vs recording of <4 indicators), was significantly (P<0.05) associated with survey year, marital status, socio-economic status, maternal antenatal TB screening, antenatal infant feeding counselling, delivery at a clinic or hospital and type of birth attendant. CONCLUSIONS: Routine patient-held infant health RtHB, a critical tool for continuity of care in high HIV/TB prevalence settings, was poorly completed, with less than 50% of the RtHB showing expected completeness. However, government efforts for improved usage of the booklet were evidenced by the near doubling of completeness from 2011 to 2013. Education about its importance and interventions aiming at optimising its use without violating user privacy should be continued.